УТОЧНЕННЯ ПАРАМЕТРІВ MATLAB МОДЕЛІ ОБМЕЖУВАЧА ПЕРЕНАРУГИ - Шполянський, О.Г. (Інститут електродинаміки НАН України, Київ, 2020)
This article proposes a method for the parameters adjustment of the Matlab Simscape library Surge Arrester block. It is based on building of nonlinear V-I characteristic by approximation of residual voltage and impulse current obtained from manufacturer catalogs. Given parameters of the exponential function are checked by transient simulations under impact of standard current impulses on surge arresters. References 14, figure 1, tables 3.